Bilirubin metabolism in relation to cancer - Yi, Fengyun; Tao, Siyu; Wu, Hongze (Frontiers in Oncology, 2025)
Bilirubin, a metabolite of hemoglobin, was long thought to be a harmful waste product, but recent studies have found it to have antioxidant and anti-tumor effects. With the extensive research on the mechanism of malignant tumor development, the antioxidant effect of bilirubin is increasingly becoming a hotspot in anti-cancer research. At present, there are two main views on the relationship between bilirubin and cancer, namely, its pro-cancer and anti-cancer effects, and in recent years, studies on the relationship between bilirubin and cancer have not been systematically summarized, which is not conducive to the further investigation of the role of bilirubin on cancer. To understand the multifaceted role of bilirubin in tumorigenesis as well as to develop more effective and affordable antitumor therapies, this review provides an overview of the effects of bilirubin on tumors in terms of oxidative, inflammatory, and cellular signaling pathways, as well as the resulting therapeutic ideas and approaches.